Impact of Exercise Training on Survival Rate and Neural Cell Death in Sepsis Through the Maintenance of Redox Equilibrium - Taewan Kim; Youngyun Jin; Jinkyung Cho; Donghyun Kim (International Neurourology Journal, 2024)
Purpose Sepsis-related deaths occur during both the early proinflammatory and the late immunosuppressive phases of the condition. The balance of pro- and anti-inflammatory responses is influenced by damaged cells that die via either proinflammatory necroptosis or anti-inflammatory apoptosis. Both forms of cell death may be mediated by reactive oxygen species (ROS) generated during the proinflammatory response. Recent evidence suggests that exercise training boosts antioxidative capacity and could offer protection against sepsis. Given these findings, we aimed to examine the impact of exercise training on neural cell death in the context of sepsis. Methods We assessed the effectiveness of exercise in reducing ROS production and the inflammatory response using a cecal ligation and puncture (CLP)-induced sepsis model. Forty C57BL/6N male mice were randomly divided into 2 groups: control (CLP-Con; n=20) and experimental (CLP-Ex; n=20). Before the induction of sepsis by CLP, the CLP-Ex mice underwent interval training on a treadmill 3 days per week for 8 weeks. Each day involved 10 cycles of 2 minutes at 8 m/min and 2 minutes at 15 m/min. After the CLP procedure, we monitored the survival of 10 mice from each group over a 30-hour period. Results The findings indicated that exercise training increased the survival rate among mice with CLP-induced sepsis by enhancing antioxidative capacity and delaying the transition from a hyperdynamic to an immunosuppressive state. Conclusions Exercise training may delay the progression from the hyperdynamic state to the hypodynamic phase of sepsis by increasing antioxidant capacity and reducing apoptotic cell death.